DESIGN AND CHARACTERIZATION OF SPIN COATER TO SUPPORT NATIONAL SEMICONDUCTOR INDUSTRY - Ardi Rahman; Okasatria Novyanto; Nurul Alfiyati; Ahmad Sidik; Irman Idris; Asep Ridwan Nugraha (Badan Standardisasi Nasional, 2019)
Recently, semiconductor industry grows rapidly due to high demand of modern electronic system. In addition, the value of investments in Indonesia electronic industries also more than doubled during 2015-2017. This increase in investment will certainly have an impact on the increasing the needs for electronic / semiconductor component processing machines. To support it, well performed spin coater then were designed. The characterization of spin coating process was done at BSN (formerly was known as Research Center for Metrology LIPI) using roughness measuring instrument/ profilometer that traceable to PTB (Germany) to guarantee the validity of the measurement results. Characterization experiment used positive photoresist SPR3018 to see the performance of system designed. Three different experiments were performed to determine the impact of spin speed and spin time to photoresist thickness and uniformity. The characterization shown that on spin speed increased, the photoresist was deployed thinner. The thickness of the photoresist is inversely proportional to the square root of spin speed. Furthermore, the longer spin coating time, it increases the tendency of concave surface. This work is expected to benefit the practitioners of electronic systems, semiconductor industries, and even SNI conceptors.